Redesain Turbin 175 KW Untuk Pembangkit Listrik Tenaga Mikrohidro (PLTMH) Desa Mekar Sari Buleleng Bali - Laksana, Dewa Putu Ari; Giriantari, Ida Ayu Dwi; Satya Kumara, I Nyoman (Majalah Ilmiah Teknologi Elektro, 2020)
The Mekar Sari Buleleng Microhydro Power Plant (MHP) has been around since 1980. This 10 kW PLTMH has experienced various problems resulting in suboptimal operation. One of the proposed improvements is a decades-old turbine redesign. The new design resulted in a crossflow turbine with a capacity of 185 kW. The performance of the turbine was validated using Computational Fluid Dynamics (CFD) software with a simulation of the average turbine power output of 175 kW. One of the improved features used in this turbine design is the nozzle design so that the turbine's output power can be maximized.